High-quality reduced graphene oxide by CVD-assisted annealing - Grimm, Stefan; Schweiger, Kai Manuel; Eigler, Siegfried; Zaumseil, Jana (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
Graphene oxide is a promising solution-processable precursor for the mass production of graphene thin films. However, during the wet chemical oxidation and reduction process toward reduced graphene oxide (rGO) a large number of defects are created. Although it is possible to synthesize rGO with an average defect distance of 3-4 nm, the performance is still limited. Here we demonstrate the partial restoration of the graphene basal plane of rGO by annealing in Ar/H2/isopropanol flow. Detailed statistical Raman analysis over large areas corroborates that the mean defect distance increases from initially 2-3 to 10-12 nm after CVD annealing. Some areas even reach defect distances of up to 18 nm. However, residual manganese impurities from the oxidation process lead to undesired carbon nanotube growth on the substrate under these conditions and had to be removed before the deposition of graphene oxide flakes on the substrate. The observed defect reduction during CVD annealing indicates that the lattice defects in rGO are mostly decorated vacancies that can be healed by addition of carbon under suitable conditions.